Nabrzeża poezji Różewicza - Pertek, Grzegorz (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2013)
In this article, the author attempts to describe the dialectical relationship between poetry and poem. This distinction seems to be as clear, as ambiguous and contradictory. The purpose of this article is therefore to unravel the problem, approaching it from two perspectives. Based on the analysis of a fragment of the poem Woda w garnuszku, Niagara i autoironia (“Water in the Pot, Niagara, and Self-Irony”), the author formulates a thesis of its illusiveness, as poem writing is a transgressive gesture, not subject to the finalization, made on the basis of an endless movement of formation and destruction. Hence the assumption that Różewicz’s only option, and even necessity, is writing. The second part of the article is devoted to the analysis of the line on the na obrzeżach poezji (“outskirts of poetry”), which addresses the problem of writing, or writability of text. The relation between poetry and poem is supplemented here by a third element, the function of the subject, which bearing the mark of the “original” act of exclusion, defines the eponymous “outskirts of poetry”, on the one hand determining the ambiguous boundary of the work (poem), and on the other – maintaining the relevance of the poem being recorded now.